PEMINDAHAN IBU KOTA NEGARA PERSPEKTIF MAQĀSHID AL-QUR’AN IBNU ‘ĀSYŪR - Romdhon, Muhammad Rizqi (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2024)
This research was carried out to know what the Ibnu ‘Āsyūr maqāshid Al-Qur’an views on the transfer of the Indonesian National Capital. This study uses a type of qualitative research. This research is descriptive in nature. This research was also carried out through library research. Based on the research that has been done, it can be concluded that the transfer of the state capital to the Archipelago Capital is a necessity that needs to be implemented because it relates to maqāshid Al-Qur’an salah al-ahwal al-'imraniyyah, and maqsad al-islah al -siyasi or politics of the people. The Archipelago Capital was established based on five principles, namely: first, Indonesia-centric. Second, sustainable smart, and green city. Third, international standard modern city. Fourth, effective and efficient governance. And finally, the fifth is economic equality in the Eastern Region. But of course, this transfer needs to be carried out carefully and with very careful consideration.